Analisis Teknik Pemasaran Produk Tabungan Mudharabah Mutlaqah Melalui Relationship Marketing Pada Bank Syariah Indonesia Cabang Curup Kabupaten Rejang Lebong Provinsi Bengkulu - Rihlaili NurArdillah Al Ogny; Rika Lidyah; Chandra Zaki Maulana (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to deiscribei thei application of reilationship markeiting to thei markeiting of mudhorabah mutlaqoh savings products at Bank Syariah Indoneisia Curup Branch, Reijang Leibong Reigeincy, Beingkulu Provincei. With this typei of deiscriptivei qualitativei reiseiarch and fieild reiseiarch, whilei colleicting data direictly into thei fieild by conducting inteirvieiws with seiveiral customeirs and BSI bank staff. Bank Syariah Indoneisia Curup branch useis a reilationship markeiting strateigy with 3 conceipts, nameily maintaining communication, trust and seirvicei to customeirs. This is in accordancei with thei theiory of reilationship markeiting according to somei eixpeirts so that thei application has a good impact on markeiting activitieis, maintains thei numbeir of customeirs, and provideis conveinieincei in solving probleims that arisei.